The Relationship Between BRI and Depressive Symptoms in Chinese Older Adults: A CLHLS‐Based Study - Yan Wang; Yuting Yang; Wanning Wang; Qiao Chen; Wangping Jia; Ling Li (International Journal of Methods in Psychiatric Research)
ABSTRACT Background There is a lack of research examining the association between obesity and depressive symptoms in relation to mental health. This study aimed to examine the correlation between Body Roundness Index (BRI) and depressive symptoms in elderly Chinese individuals. Methods The study sample consisted of 11,842 individuals aged 65 years or older from the 2018 Chinese Longitudinal Health Longevity Survey (CLHLS) database. A multivariate logistic regression analysis was used to investigate how BRI affects the likelihood of experiencing depressive symptoms, with restricted cubic spline (RCS) curves illustrating this impact. BRI values were calculated using a predefined formula for each participant, and depressive status was assessed using the Center for Epidemiologic Studies Depression Scale (CES‐D‐10). Results The mean age of the participants was 83.1 ± 10.9 years. A non‐linear relationship was identified between the BRI score and the risk of depressive symptoms. The analysis showed that for BRI scores below 5.17, there was a significant 9% increase in the risk of depressive symptoms for every 1‐point decrease in BRI score. Conversely, when the BRI was 5.17 or higher, a decrease in the BRI score did not lead to a significant increase in the risk of depressive symptoms. Conclusion The study demonstrated a significant association between BRI and depressive symptoms in elderly Chinese individuals. Furthermore, it was noted that older adults classified as overweight and mildly obese had a lower likelihood of experiencing depressive symptoms and demonstrated improved mental health.